Outreach Extensions: OMA/Rem Koolhaas Exhibitions as Self-Critical Environments. Issue 1 (2nd January 2019) - Van Gerrewey, Christophe
Abstract: Many times in the history of the Office for Metropolitan Architecture (OMA), Rem Koolhaas has self- or co-curated exhibitions of recent work—in 1978 at the Guggenheim in New York; between 1980 and 1990 in London, Amsterdam, Antwerp, Rotterdam, France, Paris, and Basel; in 1994 at the Museum of Modern Art (MoMA) in New York; and in 2003–04 in Mies van der Rohe's Neue Nationalgalerie in Berlin and in OMA's Kunsthal in Rotterdam. They are—typical for this medium—a forgotten part of OMA's production. In this article, OMA's exhibition policy is reconstructed by highlighting shows that reveal both the "medium-specificity" of an OMA exhibition as well as the obsessions in Koolhaas's method. Instead of offering the experience of "real" architectonic spaces or environments, these expositions consciously reflect the cultural and historical conditions in which OMA projects were developed, also by challenging disciplinary or institutional limits, and by "reaching out" to the world outside. A typical OMA show is not a space that has to be enjoyed phenomenologically, but rather a meaningful discursive environment, aiming to materialize the "structures" defining late twentieth-century life and work. The exhibition architecture offers guidelines for interpretation of the projects on display, as well as critical observations on the boundaries of architecture.